Measuring consumer expenditures with payment diaries - Scott Schuh (Federal Reserve Bank of Boston, 2017)
As the 2012 Diary of Consumer Payment Choice (DCPC) illustrates, there are advantages to measuring consumer expenditures by tracking the authorization of payments by instrument type (cash, check, debit or credit card, etc.). The main advantages of payment diaries appear to be the following: 1) the ability to measure expenditures by payment instrument aggregated into lumpy purchases (“shopping baskets”), 2) relatively low respondent burden, and 3) effective random sampling. Three notable results emerge from comparing the 2012 DCPC estimates with estimates from other reputable estimates of the current value of consumer expenditures: 1) DCPC payments estimates are 75 percent higher than Consumer Expenditure Survey estimates; 2)DCPC consumption estimates are 17 percent higher than personal consumption expendituresestimates in comparable expenditure categories (about half of the categories are comparable); and 3) DCPC payments roughly equal comparably adjusted national income and product accounts disposable income.
Keywords: E21; D12; D14; 330; payments; consumer expenditures; consumption; income; diary survey